STRATEGI PEMBELAJARAN SEKOLAH MINGGU YANG EFEKTIF MENINGKATKAN ANTUSIAS ANAK MENGIKUTI IBADAH ONLINE DI GEREJA BAITHANI KAHAL SEMARANG - Soewarto Tjokrohandoko; Tantri Yulia; Eni Rombe (STT Kristus Alfa Omega, 2021)
Abstract The learning strategy from sunday school is the teacher's strategy to achieve learning objectives by setting interesting learning materials, choosing methods that can develop learning activities, using media that support learning, and applying certain approaches. There are indications that the implementation of learning strategies at Kahal Kids has not been maximized, so a study was conducted to determine the value of the learning strategies from sunday school in increasing children's interest in participating in online Sunday school worship at Baithani Kahal Church Semarang. After analyzing the data, concluded that the learning strategy from sunday school in increasing children's interest in participating in online Sunday school worship at Gereja Baithani Kahal Semarang is 81.4% or very high. Furthermore, the demonstration method that Sunday children are most interested in is online worship, with a value of 90.4% or very high.